Efficient Decontamination: Caffeine/Triclosan Removal Using Rice Husk in Batch and Fixed-Bed Columns - Villamar-Ayala, C (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Abundant, easily accessible, and low-cost agro-industrial residues represent attractive alternatives for removing emerging contaminants from water. In this work, the aqueous adsorption of caffeine/triclosan onto rice husk (RH) was studied in batch and continuous processes. For this purpose, adsorbents with three particle size ranges (120–150, 300–600, 800–2000 µm) were prepared and evaluated. The composition, structure, surface morphology, functionality, and specific surface area of the RH biosorbents were determined. This characterization revealed that RH primarily consists of lignin, cellulose, and hemicellulose, making up to 80.1% of its composition. RH also exhibited an irregular surface, with several functional groups (OH, C=O, CH, C=C, C-OH), and a relatively small specific surface area (1.18 m2/g). Batch tests were carried out using different RH sizes, doses (1–50 g/L), and contact times (5–300 min), using 20 mL of caffeine/triclosan solutions (30 mg/L). Tests were conducted to fit the most adequate kinetics and isotherm models. The optimal doses (g/L) for caffeine and triclosan removal were 4.5 and 1.5 with small RH, 8.5 and 2.5 with medium RH, and 50.0 and 10.0 with large RH, respectively. The optimal contact times for all three particle sizes were 180 and 60 min. Triclosan removal was greater than that of caffeine (2.5–25.5%) with all three particle sizes, requiring less adsorbent (2.5–5.0 times) and shorter times (3 times). The experimental data fit better the Sips isotherm and Elovich kinetics models. The small (120–150 µm) particles achieved the highest caffeine/triclosan batch adsorption capacities (6.3/28.6 mg/g). Continuous tests were performed on fixed-bed columns of 1 cm in diameter, packed with 4, 5, and 8 cm of RH, operated with hydraulic loading rates between 2 and 4 m3/m2day. Small particles also reached the highest adsorption capacity in the removal of caffeine (352.7 mg/L) and triclosan (3797.2 mg/L), and the experimental data were well-fitted to the Bohart–Adams model. The research results not only demonstrate the effective removal of contaminants but also illustrate the versatility and applicability of rice husk in various conditions and systems. © 2023 by the authors.